Dense ceramic electrolyte 3D printing via digital light processing for solid oxide cells - Ng, Desmond Zhi Xiong (Nanyang Technological University, 2023)
Additive manufacturing techniques could open possibilities to reduce the complexities of Solid Oxide Fuel Cells (SOFCs). The focus of this work is on the fabrication of dense 8 mol% yttria-stabilized zirconia (8YSZ) ceramics through DLP (digital light processing) stereolithography method. The printing of green body up to a solid loading of 30 vol% for the ceramic resin suspension have been demonstrated. A microstructure analysis was performed on the specimens at different magnifications and the results were analyzed. Improving the formulation concentration and procedure of ceramic resin suspension showed great improvements in microstructure properties of the specimen after debinding and sintering process. Dispersant was added during the suspension preparations to improve the dispersion of 8 mol% yttria-stabilized zirconia (8YSZ) particles. Addition of pressure during the debinding and sintering process was able to further improve the microstructure of the specimen. This project demonstrated the potential to fabricate dense electrolyte for SOFCs via DLP-3DP and pressure sintering process.